Within‐Plant Leaf Maturity and Trichome Density Variation Shape the Elemental Composition Divergence in Desert Plant Sand Rice (Agriophyllum squarrosum) - Ruilan Ran; Xiaoyun Cui; Xin Zhao; Yingxue Zhao; Caixia Zhang; Pengshan Zhao (Ecology and Evolution)
ABSTRACT Subindividual variation in leaf elemental composition, driven by trichome density and leaf maturity, is critical for plant adaptation but poorly understood in desert species. Here, we reveal that sand rice (Agriophyllum squarrosum), a potential future food crop, exhibits obvious declines in leaf trichome density across developmental stages, significantly influencing the redistribution of 33 mineral elements. The concentrations of these elements varied between genotypes (wild type: Shapotou, SPT; trichomeless1 mutant: astcl1) and/or across leaf ages (top, middle, bottom). Sixteen key elements (e.g., S, Ca, Fe, Mn) were identified as primary factors of elemental variance. Our findings reveal a specific subindividual mineral composition of sand rice influenced by trichome density and leaf maturity, providing insights into adaptive trends in leaf nutrient traits and enhancing our understanding of the strategies plants employ to thrive in barren sandy environments.